Algal turf scrubber (ATS) floways on the Great Wicomico River, Chesapeake Bay: productivity, algal community structure, substrate and chemistry1. Issue 3 (25th March 2013) - Adey, Walter H.; Laughinghouse, H. Dail; Miller, John B.; Hayek, Lee‐Ann C.; Thompson, Jesse G.; Bertman, Steven; Hampel, Kristin; Puvanendran, Shanmugam; Buschmann, A.
<x xml:space="preserve">Abstract</x> Two Algal Turf Scrubber (ATS) units were deployed on the Great Wicomico River (GWR) for 22 months to examine the role of substrate in increasing algal productivity and nutrient removal. The yearly mean productivity of flat ATS screens was 15.4 g · m−2 · d−1. This was elevated to 39.6 g · m−2 · d−1 with a three‐dimensional (3‐D) screen, and to 47.7 g · m−2 · d−1 by avoiding high summer harvest temperatures. These methods enhanced nutrient removal (N, P) in algal biomass by 3.5 times. Eighty‐six algal taxa (Ochrophyta [diatoms], Chlorophyta [green algae], and Cyan‐obacteria [blue–green algae]) self‐seeded from the GWR and demonstrated yearly cycling. Silica (SiO2) content of the algal biomass ranged from 30% to 50% of total biomass; phosphorus, nitrogen, and carbon content of the total algal biomass ranged from 0.15% to 0.21%, 2.13% to 2.89%, and 20.0% to 25.7%, respectively. Carbohydrate content (at 10%–25% of AFDM) was dominated by glucose. Lipids (fatty acid methyl ester; FAMEs) ranged widely from 0.5% to 9% AFDM, with Omega‐3 fatty acids a consistent component. Mathematical modeling of algal produ‐ctivity as a function of temperature, light, and substrate showed a proportionality of 4:3:3, resp‐ectively. Under landscape ATS operation, substrate manipulation provides a considerable opportunity to increase ATS productivity, water quality amelioration, and biomass coproduction for fertilizers, fermentation energy, and omega‐3 products. Based on the 3‐D prod‐uctivity and algal chemical composition demonstrated, ATS systems used for nonpoint source water treat‐ment can produce ethanol (butanol) at 5.8× per unit area of corn, and biodiesel at 12.0× per unit area of soy beans (agricultural production US).